PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KATINGAN - Royen Bertoni Sitorus; Ahmad Alim Bachri (JWM (JURNAL WAWASAN MANAJEMEN), 2014)
This study aims to identify and analyze the influence of work motivation (X1) and work discipline (X2) as independent variables either simultaneously or partially on the performance of the employee Department of Transportation, Communication and Information Katingan. As well as to determine, which dominant variable effect on performance employees. The methods of this research are using questionnaires with a sample of 63 employees of the Department of Transportation, Communication and Information Katingan. Measurement variables using Likert scale with a score of 1 to 5. To determine the effect of work motivation variables (X1) and work discipline variable (X2) on employee performance, using by linear regression analysis and to test the significant level using the F test and t-test with SPSS . The results simultaneously and partially suggests that work motivation variables (X1) and work discipline variable (X2) significant positive effect on employee performance (Y). The results of the study also showed, that motivational variables (X1) is the most dominant variables on performance Department of Transportation employee, Communication and Information Katingan